Exploring the Role of AI in Mitigating Climate Change (Journal of responsible AI & ethics, 2026)
Artificial Intelligence (AI) has the potential to revolutionize efforts to mitigate climate change by improving efficiency in energy management, advancing sustainable practices, and optimizing resource utilization. The increasing deployment of AI technologies across sectors like energy, agriculture, and transportation can lead to substantial reductions in carbon emissions and environmental degradation. This paper explores the role of AI in addressing climate change, examining how AI-driven innovations can be utilized to develop intelligent systems that enhance climate action strategies, including carbon capture, renewable energy integration, and environmental monitoring. By reviewing existing AI applications, case studies, and theoretical frameworks, the paper assesses the effectiveness of these technologies in mitigating climate impacts and explores ethical considerations, such as the fairness, transparency, and accountability of AI systems in global climate solutions. The study concludes by providing recommendations for harnessing AI’s potential while ensuring responsible and equitable deployment in climate change mitigation efforts.